Isolation and identification of mycorrhizal helper bacteria of Vaccinium uliginosum and their interaction with mycorrhizal fungi - Yang, Zhiyu; Dong, Hui; Zhang, Sai; Jiang, Jing; Zhu, Haifeng; Yang, Hongyi; Li, Lili (Frontiers in Microbiology, 2023)
Mycorrhizal helper bacteria (MHB) can promote mycorrhizal fungal colonization and form mycorrhizal symbiosis structures. To investigate the effect of interactions between mycorrhizal beneficial microorganisms on the growth of blueberry, 45 strains of bacteria isolated from the rhizosphere soil of Vaccinium uliginosum were screened for potential MHB strains using the dry-plate confrontation assay and the bacterial extracellular metabolite promotion method. The results showed that the growth rate of mycelium of Oidiodendron maius 143, an ericoid mycorrhizal fungal strain, was increased by 33.33% and 77.77% for bacterial strains L6 and LM3, respectively, compared with the control in the dry-plate confrontation assay. In addition, the extracellular metabolites of L6 and LM3 significantly promoted the growth of O. maius 143 mycelium with an average growth rate of 40.9% and 57.1%, respectively, the cell wall-degrading enzyme activities and genes of O. maius 143 was significantly increased. Therefore, L6 and LM3 were preliminarily identified as potential MHB strains. In addition, the co-inoculated treatments significantly increased blueberry growth; increased the nitrate reductase, glutamate dehydrogenase, glutamine synthetase, and glutamate synthase activities in the leaves; and promoted nutrient uptake in blueberry. Based on the physiological, and 16S rDNA gene molecular analyses, we initially identified strain L6 as Paenarthrobacter nicotinovorans and LM3 as Bacillus circulans. Metabolomic analysis revealed that mycelial exudates contain large amounts of sugars, organic acids and amino acids, which can be used as substrates to stimulate the growth of MHB. In conclusion, L6 and LM3 and O. maius 143 promote each other's growth, while co-inoculation of L6 and LM3 with O. maius 143 can promote the growth of blueberry seedlings, providing a theoretical basis for further studies on the mechanism of ericoid mycorrhizal fungi-MHB-blueberry interactions. It laid the technical foundation for the exploitation of biocontrol strain resources and the development of biological fertilizer.